Wirebound Boxes from Bamboos - Tandon, R. C.; Singh, J. B.; Singh, Dhyan (Indian Forester, 1988)
Tbis paper views suitability of bamboo as an alternative material for packaging purposes upto 20 kg distributed load. Two types of wirebound boxes using 'u' pins, bamboo battens and strips have been described. Strength of these boxes were compared with conventional wooden boxes as well as wire bound wooden veneer boxes. As compared to conventional wooden boxes wire bound bamboo boxes have given better results in flat drop test but slightly lower results in case of top-bottom compression. However, wire bound bamboo box had about 1.9 times the safe value of 800 kg for top-bottom compression test for the transportation and storage of distributed load up to 20 kg. It was found that wirebound bamboo boxes are better in their capacity to withstand flat drops and top-bottom compression than the wirebound wooden veneer boxes from poplar (Populus ciliata). Wirebound bamboo boxes are collapsable, reusable and require no machinery for their manufacture. They may better suit our rural people.